Production/morphological characters relationship in rubber tree progenies - Gonçalves, Paulo de Souza; Bortoletto, Nelson; Martins, Antonio Lúcio Mello; Santos, Wagner Rodrigues dos; Bidóia, Márcio Aurélio Pitta (Pesquisa Agropecuaria Brasileira, 1998)
The objective of this study was to estimate the genotypic, phenotypic and environmental correlation coefficients in 22 half-sib progenies of rubber trees [Hevea brasiliensis (Willd. ex Adr. de Juss.) Müll. Arg.]. The studied characters were: dry matter yield (PBS), girth perimeter (CC), petiole length (CP), petiole index (IP), leaflet length (CF), leaflet diameter (DF), leaflet length (CF), leaflet width (LF), leaf area (AF), foliar index (IF). The trial was placed at Experimental Station of Votuporanga (São Paulo State - Brazil) under randomized complete blocks design with five replicates and ten plants per plot. The results indicated significative differences for all studied characters. High coefficients of correlation were found. For most of the characters the genotypic correlations were higher than the phenotypic ones, indicating large influence of genetic than the environmental components of the correlations. The estimates values of genetic correlations among PBS and CC, AF, LF, DF, CF, IF, CP and IP were 0.23; -0.27; -0.48; 0.44; 0.33; 0.05; 0.32 and -0.19. The phenotypic correlations coefficient values among PBS and the same characters were 0.12; -0.05; -0.12, -0.34; 0.23; 0.54; 0.12 and -0.09. The characters AF showed positive and significative genetic correlation with CP, and DF. The high value of the genotypic and phenotypic correlation coefficient between CC and IF showed the possibility of obtaining vigorous plants through high foliar index values.
Keywords: Hevea brasiliensis; genetic variance; genotypic correlations; phenotypic correlation; environmental correlation